Simultaneous Determination of Four Marker Compounds in Lobelia chinensis Lour. Extract by HPLC-PDA - Beom-Geun Jo; Young-Hun Park; Ki Hyun Kim; Su-Nam Kim; Min Hye Yang (Applied Sciences, 2021)
Lobelia chinensis Lour. (L. chinensis) has traditionally been used as a treatment for snake bites, high fever, jaundice, edema, and diarrhea, and modern studies have reported its anti-inflammatory, antioxidant, and antiviral activities. L. chinensis contains various compounds, such as flavonoids and coumarins, and its flavonoid components have been identified in many studies. In this study, a high-performance liquid chromatograph equipped with a photodiode array (PDA) detector and an Aegispak C18-L reverse-phase column (4.6 mm × 250 mm i.d., 5 μm) was used to simultaneously analyze four marker components in L. chinensis for standardization purposes. HPLC-PDA (detection at 340 nm), performed using a 0.1% formic acid-water/0.1% formic acid-acetonitrile gradient, separated the four marker compounds: luteolin-7-O-β-d-glucuronopyranosyl (1→2)-O-β-d-glucuronopyranoside, clerodendrin, chrysoeriol-7-O-diglucuronide, and diosmin. The developed analytical method showed excellent linearity values (r2 > 0.9991), limits of detection (LODs: 0.376–2.152 μg/mL), limits of quantification (LOQs: 1.147–6.521 μg/mL), intra- and inter-day precisions (RSD < 1.96%), and analyte recoveries (96.83–127.07%; RSD < 1.73%); thus, it was found to be suitable for the simultaneous analysis of these four marker compounds in L. chinensis.